Expanding the Kavango-Zambezi (KAZA) TFCA: Experiences from Botswana - Webster, Kelly Celeste (Department of Environmental and Geographical Science, 2020)
Transfrontier Conservation Areas (TFCAs) have emerged in recent years to become an important means of governing conservation land across the national boundaries of contemporary states. Southern Africa’s TFCAs have developed as ‘new conservation’ spaces, which are considered to promote a more holistic approach to managing protected areas by effectively integrating conservation and development ideals. However, these initiatives require complex management structures that extend across and engage with a complex mosaic of land uses, while effectively trying to reconcile diverse ecological, social, and economic agendas. The Kavango-Zambezi (KAZA) TFCA is the largest of these initiatives extending across the borders of Angola, Botswana, Namibia, Zambia and Zimbabwe. This research traces the expansion of the TFCA from its formation in 2003 to 2018, with a particular focus on its land integration and resource management processes in Botswana. To examine this expansion, this research utilizes the concept of ‘territory’ as a lens of land control which draws attention to the ways in which land within various spaces is valued, utilized and accessed. For this research, territory provides a useful perspective with which land and resource valuation, land-use conflict and resource rights within the TFCA’s boundaries can be critically engaged with. In order to better understand the territorial expansion processes of the TFCA, this research examines firstly, the objectives of the Botswana state in terms of the growth of the TFCA; secondly, the motives behind the expansion processes; thirdly, the ways in which land under various tenure regimes is involved within the expansion processes; and finally, the impacts of these processes on local communities within these areas. The methodology adopted in this research involves (a) document analysis primarily focused on Botswana’s Integrated Development Plan (IDP) for the KAZA to understand the planned political processes of expansion; (b) GIS mapping activities to identify the areas and types of land tenure that have been integrated into the TFCA; and (c) interviews with stakeholders and local communities to understand the expansion processes on the ground. From this territorial orientation, this research demonstrates how the Botswana state has placed a strong strategic focus on the development of a luxury tourism industry based on wildlife and non-consumptive resource uses. This focus aligns with the growth of the KAZA TFCA in the region, which aims to develop the region’s tourist potential by expanding its conservation estate. Within these processes, land and natural resources are increasingly being seen as a means of revenue and capital accumulation in the KAZA region. These revaluations of land and resources have translated into changing land dynamics in areas that have been integrated into the TFCA. For communities in these areas, this has resulted in increasing resource restrictions, land-use and human-wildlife conflict, as well as a disengagement from resource management activities. These processes lead to unintended consequences in that they pit local communities against conservation agendas in the area.